2015
DOI: 10.1016/j.ridd.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Capturing neuroplastic changes after bimanual intensive rehabilitation in children with unilateral spastic cerebral palsy: A combined DTI, TMS and fMRI pilot study

Abstract: Intensive rehabilitation interventions have been shown to be efficacious in improving upper extremity function in children with unilateral spastic cerebral palsy (USCP). These interventions are based on motor learning principles and engage children in skillful movements. Improvements in upper extremity function are believed to be associated with neuroplastic changes. However, these neuroplastic changes have not been well-described in children with cerebral palsy, likely due to challenges in defining and implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 71 publications
4
50
0
4
Order By: Relevance
“…This raises the question why the efficacy of this approach does not seem to be influenced by CST connectivity pattern whereas CIMT may be. Neurophysiological assessments may help to delineate this matter 18 . However, based on the suggestions by Kuhnke and colleagues 13 the question seems not so much why HABIT could work for both groups but rather why CIMT may not be ideal for children with an ipsilateral CST.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question why the efficacy of this approach does not seem to be influenced by CST connectivity pattern whereas CIMT may be. Neurophysiological assessments may help to delineate this matter 18 . However, based on the suggestions by Kuhnke and colleagues 13 the question seems not so much why HABIT could work for both groups but rather why CIMT may not be ideal for children with an ipsilateral CST.…”
Section: Discussionmentioning
confidence: 99%
“…The responsivity of a child to a therapeutic or neuromodulation intervention resulting in changes in function such as stereognosis depends on cognition (awareness of the more-affected limb or developmental disregard, planning, organization), 25 neurological status (lesion location, tract integrity, cortical reorganization), 26 and the integration of sensory-motor feedback. 27 Therapeutically, CIMT includes directing the child’s attention toward the more-affected hand to improve performance.…”
Section: Methodsmentioning
confidence: 99%
“…Structural connectivity or white matter microstructure were only studied in children with CP and seven out of 10 studies specifically focused on the corticospinal tract (Kwon et al, 2014; Manning et al, 2016; Trivedi et al, 2008; Kim et al, 2015; Rickards et al, 2014; Bleyenheuft et al, 2015; Baek et al, 2013). Three moderate‐quality studies found that long‐term rehabilitation (> 6 months) changed structural or white matter connectivity, as assessed by tractography—an indirect measure of anatomical connectivity by either quantifying connection probability of two brain regions (probabilistic tractography) or estimating the number of streamlines between the two regions (deterministic tractography)—which correlated with functional improvement in children with CP (Chaturvedi et al, 2013; Englander et al, 2015); another study used a region‐of‐interest based analysis (Trivedi et al, 2008).…”
Section: Resultsmentioning
confidence: 99%